2011
DOI: 10.1186/1471-2482-11-38
|View full text |Cite
|
Sign up to set email alerts
|

Failure of available scoring systems to predict ongoing infection in patients with abdominal sepsis after their initial emergency laparotomy

Abstract: BackgroundTo examine commonly used scoring systems, designed to predict overall outcome in critically ill patients, for their ability to select patients with an abdominal sepsis that have ongoing infection needing relaparotomy.MethodsData from a RCT comparing two surgical strategies was used. The study population consisted of 221 patients at risk for ongoing abdominal infection. The following scoring systems were evaluated with logistic regression analysis for their ability to select patients requiring a relap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 20 publications
(35 reference statements)
2
33
1
8
Order By: Relevance
“…Існуючі алгоритми оцінки ризику виникнення усклад-нень ЗЗОМТ ґрунтуються або на оцінці змін лейкоцитар-ної формули, або на урахуванні даних індексу Алговера та інших гемодинамічних критеріїв і динаміки вмісту гострофазних білків крові та прокальцитоніну [7,9]. Роз-роблені математичні моделі розвитку ГЗЗОМТ у жінок, ін-фікованих N. gonorhaea та іншими захворюваннями зі ста-тевим шляхом передачі (ЗСШП) [3,7].…”
Section: акушерство та гінекологіяunclassified
See 2 more Smart Citations
“…Існуючі алгоритми оцінки ризику виникнення усклад-нень ЗЗОМТ ґрунтуються або на оцінці змін лейкоцитар-ної формули, або на урахуванні даних індексу Алговера та інших гемодинамічних критеріїв і динаміки вмісту гострофазних білків крові та прокальцитоніну [7,9]. Роз-роблені математичні моделі розвитку ГЗЗОМТ у жінок, ін-фікованих N. gonorhaea та іншими захворюваннями зі ста-тевим шляхом передачі (ЗСШП) [3,7].…”
Section: акушерство та гінекологіяunclassified
“…Роз-роблені математичні моделі розвитку ГЗЗОМТ у жінок, ін-фікованих N. gonorhaea та іншими захворюваннями зі ста-тевим шляхом передачі (ЗСШП) [3,7]. Крім того, в останні роки різні дослідники роблять спроби використовувати у гінекологічній практиці інтегральні шкали, розроблені для оцінки загального стану хворого в анестезіологічній та хірургічній практиці.…”
Section: акушерство та гінекологіяunclassified
See 1 more Smart Citation
“…Lamentablemente, los scores del APACHE II, el Índice de Mannheim, el MODS y el SOFA, no son clínicamente útiles para identificar a este grupo de pacientes y mas bien pueden combinarse con otros recursos, llámese datos de laboratorio, imágenes u otros parámetros fisiológicos como insumo para una correcta decisión del equipo de especialistas a cargo del paciente (9).…”
Section: Dilemma Of Reoperation a Critically Ill Patientunclassified
“…As Van Ruler et al [4] reported, APACHE-II score, SAPS-II, Mannheim Peritonitis Index (MPI), MODS, SOFA score, and the acute part of the APACHE-II score (APS) were evaluated and none of them were of clinical value in this group of patients [4]. However, these scoring systems can be combined with risk factors for IAH to develop prediction models.…”
mentioning
confidence: 99%